Revitalization Of The People's Economy Through The Red And White Cooperative Ecosystem - Pardomuan Robinson Sihombing (CV Pena Jaya Pers, 2026)
This study presents a critical, in-depth, and comprehensive analysis of the policy architecture, business model, and strategic implications of the Red and White Cooperative (KMP) program launched by the Government of Indonesia for the 2024-2029 period as the central pillar of people's economic transformation. Under the legal umbrella of Presidential Instruction Number 9 of 2025, this program targets the establishment and revitalization of 80,000 cooperative units as rural economic aggregators, vitally integrated with the Free Nutritious Meal Program (MBG). This study uses a qualitative approach, with a policy case study design, enriched by a systematic literature review and a global comparative analysis. The analysis was conducted through a multi-theoretical lens that included New Institutional Economics to dissect the structure of transaction costs; Institutional Isomorphism from DiMaggio and Powell to evaluate regulatory pressures and the risks of uniformity without substance; Stewardship Theory for aspects of managerial motivation; and the concept of Platform Cooperativism to examine digital sovereignty. The study's findings show that integrating KMP as a Nutrition Fulfillment Service Unit (SPPG) creates a captive market, which is crucial for initial cash flow. However, risk analysis reveals the potential for coercive isomorphism, which can give rise to